Association between the practice environment and missed nursing care in the emergency room - Viana Santana, Larissa Tabata [UNESP]; Pollo, Camila Fernandes [UNESP]; de Morais, José Fausto; Deplacido de Leo, Aniele Fernanda [UNESP]; de Freitas, Juliana Pierami [UNESP]; de Oliveira, Cesar; Meneguin, Silmara [UNESP] (Elsevier, 2025)
Background: The demanding and intricate practice environment affects the nursing care provided in the emergency room. Objective: To investigate the relationship between the practice environment and missed nursing care in the emergency room while identifying the impact of sociodemographic and work-related factors. Methods: A cross-sectional study was conducted involving 102 emergency room nursing staff at a public hospital in São Paulo state, Brazil. Data collection included administering the Misscare-Brazil survey and the Practice Environment Scale. Results: The sample consisted of 28 nurses and 74 nursing technicians. Most were women (n = 89; 87.3 %); the largest segment had a high school education (n = 48; 47.1 %). The mean score on the Practice Environment Scale was 2.17 (±0.60). The multivariate analysis indicated that the practice environment was influenced by workload (p < 0.001), experience in the profession (p = 0.013), experience in the sector (p = 0.029), extra hours (p = 0.005), adequate employee numbers (p = 0.001), job satisfaction (p = 0.033), satisfaction with the profession (p = 0.016), and Part A of the Misscare-Brazil survey (p < 0.001). The mean number of care omissions was 2.64 (± 0.77). It was independently associated with education level (p = 0.040), workload (p < 0.001), extra hours (p = 0.005), number of patients under care (p = 0.004), number of discharges (p = 0.010), and satisfaction with the profession (p = 0.037). Conclusion: The perception of an unfavourable practice environment impacted personal and work-related factors and was linked to missed nursing care in the emergency room.
Keywords: Emergency Care; Environment of Health Establishments; Job Satisfaction; Nursing Care; Patient Safety